The experiences of risk managers in providing emotional support for health care workers after adverse events. Issue 4 (April 2016) - Edrees, Hanan; Brock, Douglas M.; Wu, Albert W.; McCotter, Patricia I.; Hofeldt, Ron; Shannon, Sarah E.; Gallagher, Thomas H.; White, Andrew A.
Abstract : Risk managers often meet with health care workers who are emotionally traumatized following adverse events. We surveyed members of the American Society for Health care Risk Management (ASHRM) about their training, experience, competence, and comfort with providing emotional support to health care workers. Although risk managers reported feeling comfortable and competent in providing support, nearly all respondents prefer to receive additional training. Risk managers who were comfortable listening to and supporting health care workers were more likely to report prior training. Health care organizations implementing second victim support programs should not rely solely on risk managers to provide support, rather engage and train interested risk managers and provide them with opportunities to practice.